Surface modification of Mg3MnNi2 hydrogen storage electrode alloy with polyaniline. (18th May 2017) - Wang, Taimiao; Zhu, Yunfeng; Zhang, Yao; Liu, Yana; Lin, Huaijun; Chen, Wei; Li, Liquan
Abstract: In this paper, polyaniline (PANI) has been adopted to modify the surface of Mg3 MnNi2 hydrogen storage electrode alloy prepared by induction melting via chemical deposition. X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM) and Fourier transform infrared spectroscopy (FT-IR) tests were performed to investigate the phase composition and microstructure. The comprehensive analysis based on the results of XRD, SEM, TEM and FT-IR indicates that PANI with a thickness of about 10 nm has been successfully polymerized on the surface of Mg3 MnNi2 alloy. The discharge capacity retention ( R 20 ) of the Mg3 MnNi2 alloy has been increased from 13.5% to 36.2% after modification with PANI, indicating better cycling stability. The Tafel polarization curves reveal that the surface modification of Mg3 MnNi2 alloy with PANI can enhance its anti-corrosion ability. The increase of the exchange current density ( I o ) indicates that the surface activity of Mg3 MnNi2 alloy can be improved through the surface modification with PANI. However, the high rate discharge ability (HRD) test shows that the kinetic property of Mg3 MnNi2 alloy after the surface modification is declined, which is mainly due to the decline of the hydrogen diffusion in PANI, evidenced by the decreased limit current density ( I L ) obtained from the anodic polarization curves. Highlights: Polyaniline (PANI) was used to modify the surface of Mg3 MnNi2 alloy firstly. PANI has been successfully polymerized on the surface of Mg3 MnNi2 alloy particles. Discharge capacity retention (R20 ) was increased obviously after PANI modification. Modification with PANI can favor the charge-transfer reaction on the alloy surface.